Profoundly lower muscle mass and rate of contractile protein synthesis in boys with Duchenne muscular dystrophy. (11th October 2021) - Evans, William J.; Shankaran, Mahalakshmi; Smith, Edward C.; Morris, Carl; Nyangau, Edna; Bizieff, Alec; Matthews, Marcy; Mohamed, Hussein; Hellerstein, Marc
Abstract : Abstract: Boys with Duchenne muscular dystrophy (DMD) experience a progressive loss of functional muscle mass, with fibrosis and lipid accumulation. Accurate evaluation of whole‐body functional muscle mass (MM) in DMD patients has not previously been possible and the rate of synthesis of muscle proteins remains unexplored. We used non‐invasive, stable isotope‐based methods from plasma and urine to measure the fractional rate of muscle protein synthesis (FSR) functional muscle mass (MM), and fat free mass (FFM) in 10 DMD (6–17 years) and 9 age‐matched healthy subjects. An oral dose of D3 creatine in 70% 2 H2 O was administered to determine MM and FFM followed by daily 70% 2 H2 O to measure protein FSR. Functional MM was profoundly reduced in DMD subjects compared to controls (17% vs . 41% of body weight, P < 0.0001), particularly in older, non‐ambulant patients in whom functional MM was extraordinarily low (<13% body weight). We explored the urine proteome to measure FSR of skeletal muscle‐derived proteins. Titin, myosin light chain and gelsolin FSRs were substantially lower in DMD subjects compared to controls (27%, 11% and 40% of control, respectively, P < 0.0001) and were strongly correlated. There were no differences in muscle‐derived sarcoplasmic proteins FSRs (creatine kinase M‐type and carbonic anhydrase‐3) measured in plasma. These data demonstrate that both functional MM, body composition and muscle protein synthesis rates can be quantified non‐invasively and are markedly different between DMD and control subjects and suggest that the rate of contractile but not sarcoplasmic protein synthesis is affected by a lack of dystrophin. Key points: Duchenne muscular dystrophy (DMD) results in a progressive loss of functional skeletal muscle but total body functional muscle mass or rates of muscle protein synthesis have not previously been assessed in these patients. D3 ‐creatine dilution was used to measure total functional muscle mass and oral 2 H2 O was used to examine the rates of muscle protein synthesis non‐invasively in boys with DMD and healthy controls using urine samples. Muscle mass was profoundly lower in DMD compared to control subjects, particularly in older, non‐ambulant patients. The rates of contractile protein synthesis but not sarcoplasmic proteins were substantially lower in DMD. These results may provide non‐invasive biomarkers for disease progression and therapeutic efficacy in DMD and other neuromuscular diseases. Abstract : Abstract figure legend D3 ‐creatine (D3 Cr) and 2 H2 O were ingested by boys with Duchenne muscular dystrophy and healthy controls. D3 Cr is actively transported into the sarcomere and mixes with the entire creatine pool. D3 Cr is converted to D3 ‐Creatinine (D3 Crn) and rapidly excreted in urine. 2 H is incorporated into all newly synthesize protein. Proteins and peptides leak from the sarcomere and enter the circulation. Peptides from many of these newly synthesize skeletal muscle proteins are filtered in the kidney and excreted in urine. Mass spec analysis of urine D3 Crn enrichment provides a measure of total body creatine pool size and skeletal muscle mass and analysis of 2 H enrichment of urine titin and myosin light chain provides an estimate of synthesis rates.